Holistic approach to oncology patients with a special focus on physical activity – a literature review - Smuszkiewicz-Różański, Paweł; Różańska-Smuszkiewicz, Gabriela; Ragan, Dagmara; Długosz, Joanna; Staszczak, Paweł; Bara, Maciej; Kmiotek, Weronika; Jaworska, Barbara; Oronowicz, Radosław; Jama, Grzegorz (Quality in Sport, 2024)
Current global statistics indicate nearly 20 million new cancer cases and close to 10 million cancer deaths annually. Demographic forecasts predict that the annual number of new cancer cases will reach 35 million by 2050, representing a 77% increase from the 2022 levels. These statistics highlight that oncology patients will increasingly be seen by doctors of all specialties. This is a particular patient population because, primarily, they are chronically ill with a severe disease and are treated with potent medications. The focus of both the doctor and patient is usually on the disease and the primary treatment, as these constitute the main therapeutic issue. Consequently, the aspect of physical activity, which is an adjunct, may not only be deprioritized but may also be entirely overlooked. Recent studies support the promotion of physical activity and exercise for adult oncology patients before, during, and after cancer treatment, across all types of cancer, including those with advanced disease. Lack of physical activity, reduced physical fitness, including exercise intolerance, and dependency are common consequences of cancer and its treatment. The vast majority of guidelines for those diagnosed with cancer suggest that physical activity is an essential part of care. Individualization and optimization of oncological treatment significantly improve prognosis for these patients. Simultaneously, there remains a continuous need for further research into the type, intensity, and duration of physical activity for cancer prevention, as well as the development of effective recommendations for patients during active cancer treatment and in remission.